Living in exile: Daily life and international relations at SWAPO's Kongwa Camp - Christian A Williams (Kronos, 2011)
From 1964, when it was first granted by the Tanzanian government to OAU recognized liberation movements, Kongwa camp has been a key site in southern Africa's exile history. First SWAPO and FRELIMO, and later the ANC, MPLA and ZAPU, inhabited neighbouring sites near the town of Kongwa in central Tanzania, where they trained their respective members in guerrilla tactics and prepared to infiltrate their countries of origin. Despite the importance of Kongwa for any history of southern Africa's liberation struggles, few secondary sources draw attention to Kongwa as a lived space, and none consider it beyond the historiography of a particular national movement. In contrast, this essay highlights the experiences of Namibians living in an international community at Kongwa during the 1960s. Drawing on taped interviews, published memoirs, the ANC's Morogoro Papers, and Tanzanian historiography and ethnography, it argues that Kongwa shaped a social hierarchy among exiled Namibians determined by their differing abilities to form relationships with non-Namibians around the camp. The essay traces the formation of this hierarchy through histories of how Kongwa camp formed; of how Namibians related to Tanzanian officials, other liberation movement members, and local farmers there; and of how such relationships shaped the form and resolution of conflicts within SWAPO. I emphasize that these histories are obscured by southern Africa's national historiographies and that they demand a regional approach to exile which attends to the particular sites and kinds of spaces in which exiles lived.